Monitoring System for Website-Based Micro Hydro Power Plant using Firebase - Hidayat, Sidiq Syamsul; Mulyaman, Heri Bertus; Basuki, Budi; Mujahidin, Irfan; Prabowo, M. Cahyo Adi; Lestari, Melisa Yufit; Rakhman, Fikri Arif (Politeknik Harapan Bersama, 2024)
The use of electrical energy is a basic need for everyone. Micro Hydro Power Plant is one of the technologies that has developed recently. This technology has little adverse impact on the environment. This plant utilizes flowing water, discharge from water, and water pressure. The highlands or mountainous areas where there is flowing water. This water flow can be used as a driving force to drive a turbine, which is the driving force for this power plant because the generator uses a generator that requires motion power to generate electricity. Because this plant utilizes flowing water as a power source to drive a turbine and turn a generator. So basically, where there is running water, there is electricity. Moreover, micro Hydro does not need to build large reservoirs like hydropower. The purpose of making this system is to make it easier to check the condition of the MHP equipment and record the data obtained from the sensors that have been installed. This Website was successfully implemented using HTML, PHP, Firebase Database, CSS, JavaScript, JSON, etc. This Website will use the waterfall method, which consists of observation and needs analysis, system design, modeling, implementation and coding, testing, and maintenance